The ANALYZING STUDENTS' DIFFICULTIES IN SOLVING PROBABILITY PROBLEMS (CASE STUDY IN THE FIRST GRADE OF SENIOR HIGH SCHOOL: This study aims to explore the various difficulties students face in solving probability problems, particularly in the first grade of senior high school. Probability, as a fundamental branch of mathematics, often challenges students due to its abstract nature and reliance on logical reasoning. By identifying common barriers such as conceptual misunderstandings, procedural er - Erma Yanti Maulita Annisa, Rauzatul Jannah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Learning difficulties are disturbances or obstacles resulting in less-than-optimal learning outcomes. Analysing student difficulties can be done by re-examining student work and asking students to explain how they solve math problems through interviews. This study aimed to describe students' difficulties in solving probability problems of first-grade high school students. This type of research is descriptive qualitative. The subjects of this study were 20 students from two high schools in Banda Aceh. Data collection techniques in this study used tests, interviews, and documentation. The subject selection technique was based on the answers to the subject questions that were wrong and considered interesting to explore further and the subjects who could provide the most information so 2 subjects were obtained from the participants. From the data analysis and discussion results, it can be concluded that students' errors in solving probability material were caused by a lack of understanding of the concept of using and applying formulas. The cause is that students are not careful and cannot understand the meaning of the question.